A gold nanoparticle-based visual aptasensor for rapid detection of acetamiprid residues in agricultural products using a smartphone. Issue 9 (16th February 2022) - Xu, Chengnan; Lin, Mei; Song, Chaonan; Chen, Danli; Bian, Caimiao
Abstract : Based on the colorimetric analysis of gold nanoparticles and a smartphone readable strategy, a stable, sensitive, and visual method was established for rapid detection of acetamiprid residues in agricultural products. Abstract : Based on the colorimetric analysis of gold nanoparticles and a smartphone readable strategy, a stable, sensitive, and visual method was established for rapid detection of acetamiprid residues in agricultural products. By optimizing the key parameters, the detection process only took 40 minutes with good specificity. The acetamiprid aptamer can help AuNPs to resist salt-induced aggregation. Conversely, in the presence of acetamiprid, the anti-protection is weakened and the AuNPs aggregated with the color change of the solution. The photographs of the solution are recorded by the smartphone and analyzed through image processing. In the range from 25 to 300 μM the method can realize a quantitative analysis of acetamiprid, and the detection limit is about 3.81 μM. Excellent recoveries are taken in samples of cucumber, cabbage, and river water, ranging from 96.78% to 129.95%. These results show no significant difference from the results obtained by the microplate reader. What's more, the method employs a smartphone to read without the assistance of professional equipment, which greatly reduces the cost of detection, and shows a promising application prospect for on-site rapid detection of acetamiprid.